Post-Artesunate Delayed Hemolysis: Anything That Can Go Wrong Will Go Wrong—Murphy's Law - Chemutai, Beliza; Ali, Muhammed Omar; Abila, Derrick Bary; Odonga, Denis Can; Apiyo, Paska; Bongomin, Felix (My University, 2025)
In patients presenting with post-malarial anemia following intravenous artesunate treatment, post-artesunate delayed hemolysis should be considered in the differential diagnosis, even in endemic settings. Close monitoring for signs of delayed hemolysis in patients previously treated with intravenous artesunate for severe malaria, regardless of their malaria exposure history or geographic location is crucial.